Molecular Pathogenesis of Endotheliopathy and Endotheliopathic Syndromes, Leading to Inflammation and Microthrombosis, and Various Hemostatic Clinical Phenotypes Based on “Two-Activation Theory of the Endothelium” and “Two-Path Unifying Theory” of Hemostasis - Jae C. Chang (Medicina, 2022)
Endotheliopathy, according to the “two-activation theory of the endothelium”, can be triggered by the activated complement system in critical illnesses, such as sepsis and polytrauma, leading to two distinctly different molecular dysfunctions: (1) the activation of the inflammatory pathway due to the release of inflammatory cytokines, such as interleukin 6 and tumor necrosis factor-α, and (2) the activation of the microthrombotic pathway due to the exocytosis of hemostatic factors, such as ultra-large von Willebrand factor (ULVWF) multimers and FVIII. The former promotes inflammation, including inflammatory organ syndrome (e.g., myocarditis and encephalitis) and multisystem inflammatory syndrome (e.g., cytokine storm), and the latter provokes endotheliopathy-associated vascular microthrombotic disease (VMTD), orchestrating thrombotic thrombocytopenic purpura (TTP)-like syndrome in arterial endotheliopathy, and immune thrombocytopenic purpura (ITP)-like syndrome in venous endotheliopathy, as well as multiorgan dysfunction syndrome (MODS). Because the endothelium is widely distributed in the entire vascular system, the phenotype manifestations of endotheliopathy are variable depending on the extent and location of the endothelial injury, the cause of the underlying pathology, as well as the genetic factor of the individual. To date, because the terms of many human diseases have been defined based on pathological changes in the organ and/or physiological dysfunction, endotheliopathy has not been denoted as a disease entity. In addition to inflammation, endotheliopathy is characterized by the increased activity of FVIII, overexpressed ULVWF/VWF antigen, and insufficient ADAMTS13 activity, which activates the ULVWF path of hemostasis, leading to consumptive thrombocytopenia and microthrombosis. Endothelial molecular pathogenesis produces the complex syndromes of inflammation, VMTD, and autoimmunity, provoking various endotheliopathic syndromes. The novel conceptual discovery of in vivo hemostasis has opened the door to the understanding of the pathogeneses of many endotheliopathy-associated human diseases. Reviewed are the hemostatic mechanisms, pathogenesis, and diagnostic criteria of endotheliopathy, and identified are some of the endotheliopathic syndromes that are encountered in clinical medicine.